Substance use and abuse: exploring alcohol and drug issues - Mignon, Sylvia I. (Lynne Rienner, 2009)
Introduction: Substances and society -- Alcohol and alcoholism -- Drugs and drug addiction -- Children and adolescents -- Women -- Race and ethnicity -- Issues of sexual identity -- The elderly -- College drinking -- Alcohol, drugs, and the family -- Alcohol, drugs, and crime -- Screening, assessment, and diagnosis of alcohol and drug problems -- Treatment and recovery -- Policy, prevention, and practice